PENINGKATAN KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS MELALUI MODEL PEMBELAJARAN BERBASIS MASALAH BERBANTUAN AUTOGRAPH DAN GEOGEBRA DI SMA FREEMETHODIST MEDAN - Ismail Hanif Batubara (MES: Journal of Mathematics Education and Science, 2017)
This research is aimed to know: (1) Whether the increasing of mathematical concept understanding ability students through problem-based learning model assisted Autograph better than the increasing of mathematical concept understanding ability students through problem-based learning model assisted Geogebra, (2) How the interaction between learning and early math  ability of student mathematical concept understanding, The population are all students of SMA Free Methodist Medan. Then randomly selected two classes of four classes. The first experimental class were treated by problem-based learning model with assisted Autograph and the second experimental grade treated by problem-based learning model with assisted Geogebra. Data analysis was performed by analysis of variance (ANOVA) and two lanes. The research shows that: (1) The increasing of mathematical concept understanding abilities students through problem-based learning model assisted Autograph better than the increasing of mathematical concept understanding abilities students through problem-based learning model assisted Geogebra. (2) There is no Interaction between learning and early math ability of student mathematical concept understanding ability.